Dislocation structure during microindentation. (September 2015) - Baitsch, M.; Le, K.C.; Tran, T.M.
Abstract: Within the recently proposed continuum dislocation theory, numerical simulations of the displacement controlled wedge indentation for single crystals using the finite elements are provided. Under the assumption of plane strain deformation of the crystal having only one active slip system on each side of the wedge the load–displacement curve as well as the dislocation density are computed for the loading and unloading path in terms of the indentation depth. The results of numerical simulations are compared with those obtained from the experiments which shows qualitative agreement.